Mössbauer, XRD, and Complex Thermal Analysis of the Hydration of Cement with Fly Ash - Vili Lilkov; Ognyan Petrov; Yana Tzvetanova; Plamen Savov; Milen Kadiyski (Journal of Spectroscopy)
Hydration of cement with and without fly ash is studied with Mössbauer spectroscopy, XRD, and thermal analysis. Iron in cement is present as Fe3+-ions and occupies two octahedral positions, with close isomer shifts and quadrupole splittings. Iron in fly ash is present as Fe2+ and Fe3+, and the Mössbauer spectra display three doublets—two for Fe3+ in octahedral coordination and one for Fe2+. A third doublet was registered in the hydrating plain cement pastes after the 5th day, due to Fe3+ in tetrahedral coordination in the structure of the newly formed monosulphate aluminate. In cement pastes with fly ash, the doublet of tetrahedral iron is formed earlier because the quantity of ettringite and portlandite is low and more monosulphate crystallizes. No Fe(OH)3 phase forms during hydration of C4AF. The fly ash displays pozzolanic properties, which lead to lowering of the portlandite quantity in the cement mixtures and increasing of the high temperature products.